And the first runner-up is...: comparing winner selection procedures in multi-winner Tullock contests - Subhasish M. Chowdhury; Anwesha Mukherjee; Theodore L. Turocy (Review of Economic Design, 2022)
We characterise the strategic equivalence among k -winner contests using simultaneous and sequential winner selection. We test this prediction of strategic equivalence using a series of laboratory experiments, contrasting 1-winner contests with 2-winner contests, varying in the latter whether the outcome is revealed sequentially or in a single stage. We find that in the long run, average bidding levels are similar across strategically-equivalent contests. However, adaptation in 2-winner contests is slower and less systematic, which is consistent with the property that simultaneous winner selection results in outcomes that are more random than in the 1-winner case.
Keywords: C72; C91; D72; D82; 330; Lottery contest; Multi-winner contests; Learning; Experiment; Strategic equivalence